2010
DOI: 10.1016/j.freeradbiomed.2009.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zinc deficiency increases oxidative DNA damage in the prostate after chronic exercise

Abstract: Approximately 12% of Americans do not consume the recommended level of zinc and could be at risk for marginal zinc deficiency. Zinc functions in antioxidant defense and DNA repair and could be important for prostate health. We hypothesized that marginal zinc deficiency sensitizes the prostate to oxidative stress and DNA damage. Rats were fed a zinc-adequate (ZA; 30 mg Zn/kg) or marginally zinc-deficient (MZD; 5–6 mg Zn/kg) diet for 6 weeks. MZD increased p53 and PARP expression but no change in 8-hydroxy-2′-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…Epidemiological studies have revealed associations between low blood Zn concentrations and an increased risk of sepsis (2) and cancer (28). Consistent with literature reporting human IBD, experimental animals with marginal Zn deficiency after chronic exercise exhibit oxidative DNA damage in the prostate (25). It has also been shown that marginally Zn-deficient rats experience increased susceptibility to acute lipopolysaccharide (LPS)-induced liver injury (24).…”
mentioning
confidence: 60%
“…Epidemiological studies have revealed associations between low blood Zn concentrations and an increased risk of sepsis (2) and cancer (28). Consistent with literature reporting human IBD, experimental animals with marginal Zn deficiency after chronic exercise exhibit oxidative DNA damage in the prostate (25). It has also been shown that marginally Zn-deficient rats experience increased susceptibility to acute lipopolysaccharide (LPS)-induced liver injury (24).…”
mentioning
confidence: 60%
“…There have been some studies investigating the association of dietary supplement use with prostate cancer risk. Multivitamin use (Lawson et al, 2007) and calcium intake (Butler et al, 2010) are known to increase the risk of prostate cancer, while selenium (Lindshield et al, 2010) and zinc (Song et al, 2010) showed in-vitro inhibitory effects on the growth of prostate cancer cells and decreased oxidative DNA damage in the prostate, respectively. Considering that this study showed no association of vitamin intake with increased PSA, vitamin use might increase the risk of prostate cancer without elevation of serum PSA.…”
Section: Discussionmentioning
confidence: 99%
“…higher BER activity immediately after birth [52,53] subjected to a marginal zinc deficiency, and in combination with chronic exercise, there was an increase in DNA oxidation [44]. Activities of PARP as well as DNA polymerase b and DNA ligase, three enzymes induced in rat liver by aflatoxin B1-treament were higher in rats deficient in vitamin A [45] or copper [46] and were brought down by supplementation.…”
Section: Animal Studies Of the Effect Of Micronutrients On Dna Repairmentioning
confidence: 99%